Use of termite (Glyptotermes montanus) as poultry feed - Ketaren, P.P; Sinurat, A.P; Purwadaria, T; Kompiang, I.P; Amir, M (Indonesian Animal Sciences Society, 2001)
Termites containing high protein and various enzymes including cellulase enzyme produced by microbes in its digestive system. An experiment was conducted to evaluate the use of termite (Glyptotermes montanus) as poultry feed. One hundred and seventy five, day-old broiler chicks were used for this experiment. The broiler chickens were allotted to seven different diets: (1) control diet containing rice bran without termite (KD), (2) KD + 0.75% dried termites (RK), (3) KD + 1.50% RK, (4) KD + 3.00% RK, (5) KD + 14% fresh termite (RB), (6) KD + 4.29% RB, (7) KD + 8.57% RB. Feed intake, weight gain, feed conversion ratio (FCR), mortality, carcass and visceral were recorded for five weeks experiment. The results showed that chickens fed the diet containing 1.50% RK grew significantly (P<0.05) bigger than other diets. Feed intake of chickens fed KD + 1.50% RK was also significantly (P<0.05) higher than chickens fed other diet but was not significantly (P>0.05) different from feed intake of chickens fed KD, KD + 3.00% RK and KD + 8.57% RB. FCR of chickens fed RK or RB were not significantly different (P>0.05) from FCR of KD diet. Carcass weight of broiler chickens fed KD + 1.50% RK significantly (P<0.05) higher than carcass weight of chickens fed KD diet or improved carcass percentage of about 4.4%. This experiment also showed that the inclusion of termites in the diet significantly (P<0.05) increased percentage of gizzard, heart and abdominal fat weight of chickens. Â Key words: Termite, feed ingredient, broiler chicken, carcass